The historical configuration of public school teachers in Colombia: from oppression to subordination, 1870-2002 - Saldarriaga Vélez, Oscar de Jesús; Vargas, Claudia María (Historia y Memoria de la Educación, 2015)
This article takes a brownian approach to the history of Columbia, tracing the configuration of the structural role played by schoolteachers (the teacher as subject) and in particular the three facets of their profession: as knowledge-makers, as public subjects and as social subjects. In all three instances they are subjected to the impulses of government power, pastoral power, political parties and union forces from within their profession. The article focuses on the fundamental changes in schoolteachers’ struggles, which move from the social demands of the oppressed (taken at large) to their struggles as specific, subordinate knowledge-makers.